Immunotherapy in gynecological cancers - Domenica Lorusso; Valentina Ceni; Gennaro Daniele; Antonella Pietragalla; Vanda Salutari; Margherita Muratore; Camilla Nero; Francesca Ciccarone; Giovanni Scambia (Open Exploration Publishing Inc., 2021)
Immunotherapy has changed the natural history of several malignancies that, a decade ago, had a very poor prognosis, such as lung cancer and melanoma. Consequently, many attempts have been done to expand the indications of immunotherapy agents, predominantly immune checkpoint inhibitors (ICIs), in other cancers, including gynecological malignancies. Alongside promising results in cervical and endometrial neoplasms, there are not clear data on the benefit of ICIs as single agent or in combination with antiangiogenic agents in ovarian cancer (OC) and ongoing trials are focusing on combining ICIs with standard chemotherapy or PARP inhibitors. This chapter summarized the evidences of ICIs in gynecological malignancies and report the ongoing trials in cervical, endometrial and OC.